2017
DOI: 10.5811/westjem.2017.5.34099
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Mechanical Ventilation in the Emergency Department

Abstract: IntroductionDue to hospital crowding, mechanically ventilated patients are increasingly spending hours boarding in emergency departments (ED) before intensive care unit (ICU) admission. This study aims to evaluate the association between time ventilated in the ED and in-hospital mortality, duration of mechanical ventilation, ICU and hospital length of stay (LOS).MethodsThis was a multi-center, prospective, observational study of patients ventilated in the ED, conducted at three academic Level I Trauma Centers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…Several studies defined a time threshold a priori as greater than 2, 4, or 6 hours 16,29‐31 . Two studies assessed boarding based only on the total number of hours an intubated patient spent in the ED 19,32 . The DELAY‐ED study group identified 6 hours in the ED (from time of arrival at triage) as the definition of ED boarding, based primarily on their observations that adverse outcomes among admitted critically ill patients are more common with an ED stay greater than 6 hours 31 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies defined a time threshold a priori as greater than 2, 4, or 6 hours 16,29‐31 . Two studies assessed boarding based only on the total number of hours an intubated patient spent in the ED 19,32 . The DELAY‐ED study group identified 6 hours in the ED (from time of arrival at triage) as the definition of ED boarding, based primarily on their observations that adverse outcomes among admitted critically ill patients are more common with an ED stay greater than 6 hours 31 .…”
Section: Resultsmentioning
confidence: 99%
“…Both retrospective and prospective observational studies demonstrate worse outcomes for critically ill patients after ED boarding (Supplemental Table 2, Supplemental Digital Content 1, http://links.lww.com/CCM/F477), including increased duration of mechanical ventilation, longer ICU length of stay, and higher mortality 16,18,19,31,32,38,39 . Increased ED boarding times are associated with worsening organ dysfunction and a four‐fold increase in the probability of poor neurologic recovery in patients presenting with stroke 38 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Related care to bronchial aspiration prevention Keep the headboard elevated between 30 and 45°1 [7][8][9][10][11][12][13][14][15][16][17][18][19] IIb, VI…”
Section: Endotracheal Tube Carementioning
confidence: 99%
“…6 Although these patients may benefit from immediate transfer to an ICU, this option is limited by overcrowding and scarce resources, which justifies the implementation of patient-directed care on mechanical ventilation in HE. 7 Mechanical ventilation totally or partially replaces spontaneous ventilation and is indicated in acute respiratory failure (ARF) or acute-on-chronic. When used invasively, endotracheal tube or tracheostomy tube is used.…”
Section: Introductionmentioning
confidence: 99%